PENGEMBANGAN MODUL ELEKTRONIK BERBASIS MODEL LEARNING CYCLE 7E PADA POKOK BAHASAN FLUIDA DINAMIK UNTUK SISWA SMA KELAS XI - Ghaliyah, Sitti; Bakri, Fauzi; Siswoyo, Siswoyo (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This developing study found an independent learning material in the form of physics electronic module in the basis of learning cycle 7E in Dynamic Fluid subject. The method used in this study is development research with development stages of ADDIE (Analyze, Design, Development, Implementation, and Evaluation). Physics electronic module in the basis of learning cycle 7E, through validation examination steps, has reached the scale achievement of 94,09% by physics experts, 93,64% by learning media experts, 82,79% by learning experts, and 95,23% by physics teachers of Senior High School students. The result in the experiment of 11th grade of high school students has reached the sacle achievement of 84,45%. There are 35 grader of 51 respondents have interest to do first comprehension exercise, formative test and summative evaluation that is prepared in physics electronic module in the basis of learning cycle 7E. As a result, physics electronic module in the basis of learning cycle 7E in Dynamic Fluid subject fills the requirement with a very high quality to be used as an independent learning material for 11th grade of Senior High School students. Keywords: An independent learning material, Learning cycle 7E model, Physicselectronic module.